Covid-19 Vaccination and Tinnitus (Case Report) - Fatemeh Moghadasi Boroujeni; Mehdi Ghadiri (Journal of Kerman University of Medical Sciences, 2023)
Background: The Covid-19 disease was first observed in December 2019 and became a big challenge for the World Health Organization in a short period of time. Getting infected with Covid-19 has very dangerous complications and is considered a serious threat to people's health. One of the most important ways to prevent this disease is vaccination. Like other vaccines, the Covid-19 vaccines also have various side effects, The side effects of existing vaccines are usually mild and transient, and the side effects related to hearing are very rare.Case report: In this study, we have presented a report of a 40-year-old woman with a complaint of tinnitus 24 hours after the injection of the second dose of Sinopharm vaccine. The patient did not have any history of hearing problems or tinnitus before the vaccine injection. According to the results of the evaluations, the necessary counseling regarding tinnitus, sound therapy and counseling sessions were provided to reduce the patient's anxiety. After one month, the patient was very satisfied with the cessation of tinnitus.Conclusion: tinnitus without hearing loss is reported as a rare side effect of vaccination. Since the exact mechanism of tinnitus after vaccination is not fully clear yet, there is a need for more studies in this field.